Extremely Low Frequency (0.1 to 1.0 mHz) Surf Zone Currents - Steve Elgar; Britt Raubenheimer; David B. Clark; Melissa Moulton (Geophysical Research Letters)
Abstract Low‐frequency surf zone eddies disperse material between the shoreline and the continental shelf, and velocity fluctuations with frequencies as low as a few mHz have been observed previously on several beaches. Here spectral estimates of surf zone currents are extended to an order of magnitude lower frequency, resolving an extremely low frequency peak of approximately 0.5 mHz that is observed for a range of beaches and wave conditions. The magnitude of the 0.5‐mHz peak increases with increasing wave energy and with spatial inhomogeneity of bathymetry or currents. The 0.5‐mHz peak may indicate the frequency for which nonlinear energy transfers from higher‐frequency, smaller‐scale motions are balanced by dissipative processes and thus may be the low‐frequency limit of the hypothesized 2‐D cascade of energy from breaking waves to lower frequency motions.